6 - Sciences sociales et société : Le cas du Nigeria - KODJO, Samuel (Africa Development, 1980)
In this article the author is trying to see how social sciences as means of collecting «reliable informations about the conditions determining social existence in specific environments and of working out strategies corresponding to the same conditions», have affected the Nigerian environment. In his introductory remarks he makes a number of important points : What makes social scientific work difficult is that although it deals with society at large, there are some important elements of this complex reality which are non-material, unseen and somehow trans cendental and which social scientists can hardly apprehend. Due largely to the invisible nature of society and its mechanisms of functioning, the problem of objectivity of value-neutrality and its attendant questions of impartiality and ideology have always plagued social scientists in their sustained efforts at explaining social realities. The writer then proceeds by pointing out that social sciences are derived from a particular mode of social production. Hence the importance of science in general and social sciences in particular as an important input for economic and political decision making processes in societies. In the so-called complex societies there is a systematic alienation of science from society at large, partly because of the alliance between science producing agencies and the powerful economic and political groups. After this theoretical analysis of the relationships between Social Sciences and society, the author tries to analyse the Nigerian case in the light of this theoretical point of view. After the creation of the West African Institute of Social and Economic Research (WAISER) and its offspring the Nigerian Institute of Social and Economic Research (NISER), the investiga tion of «Society» was geared towards the identification of those problems which would enable the (colonial) regime to carry out its civilising mission to the «natives». This institutionalisation of social sciences has had the fol lowing consequences: The Nigerian Social Scientist tended to focus their attention on the so-called applied social science. In doing this they accepted some basic assumptions of conventional social science, such as: a) The conventional «orthodox» or «liberal» economic theory is un restrictedly accepted as satisfactory in absolute terms. b) The exclusive interest in small-scale industries presupposes an un derstanding according to which the prevailing international division of labour is appropriate to Nigeria. c) The international division of labour does not contain any serious historical deterministic biases which favour the position of develop ped countries. As a result conventional social science such as sociology, political sciences and economics became incapable of relevant analyses of the Nige rian context. Finally, in the last part of this article, the author suggests a number of proposals for a problem oriented use of social sciences in Nigeria. Samuel KODJO, Professeur au Département des Sciences Economiques, Université de Nsukka, Nigéria — (Juin 1979)·